Innovative strategies and challenges mosquito-borne disease control amidst climate change - Zhang, Yuan; Wang, Minhao; Huang, Mingliu; Zhao, Jinyi (Frontiers in Microbiology, 2024)
The revival of the transmission dynamics of mosquito-borne diseases grants striking challenges to public health intensified by climate change worldwide. This inclusive review article examines multidimensional strategies and challenges linked to climate changes and the epidemiology of mosquito-borne diseases such as malaria, dengue, Zika, chikungunya, and yellow fever. It delves how the biology, pathogenic dynamics and vector distribution of mosquito are influenced by continuously rising temperatures, modified rainfall patterns and extreme climatic conditions. We also highlighted high likelihood of malaria in Africa, dengue in Southeast Asia and blowout of Aedes in North America and Europe. Modern predictive tools and developments in surveillance including molecular gears, Geographic Information Systems (GIS) and remote sensing have boosted our capacity to predict epidemics. Integrated data management techniques and models based on climatic conditions provide a valuable understanding for public health planning. Based on recent data and experts ideas, the objective of this review is to provide a thoughtful understandings of existing landscape and upcoming directions in the control of mosquito-borne diseases regarding changing climate. This review determines emerging challenges and Innovative vector control strategies in the changing climatic conditions to ensure public health.